The Relationship Between Emotional Intelligence with Students' Learning Independence at SMA PGRI 3 Padang - Eka Putri, Diana (Jurnal Riset Ilmu Pendidikan, 2022)
The aims of this research are to described 1) Overview of emotional intelligence, 2) Overview of learning independence, 3) The correlation between this emotional intelligence and learners' learning independence. The type of research is descriptive research. The population in this study was all students of class X, XI, XII which amounted to 69 students. Sampling using Total Sampling techniques. Data was analysis by using the score percentage formula and Person’s Product Moment Correlation. The results of this study are 1) The emotional intelligence of learners is in the high categori’s , 2) The learning independence of learners is in the high categoryi’s, 3) The was correlation between of emotional intelligence with the learning learners of independence is the strong coefficient correlation and as well as  in the indicator.Based on the find of this study, it is recommended to theconselor to of this student improve emotional intelligence and learning independence